Pengolahan Sampah Organik melalui Biopori sebagai Upaya Lingkungan Bersih dan Tanah Subur di Desa Pematang Guntung Kecamatan Teluk Mengkudu Kabupaten Serdang Bedagai - Siti Nurhaliza; Ayu Anjalina; David Pratama; Andika Nugroho Ramadhan; Ibnu yahdi khoir; Evand Abygayl Siahaan; M. Husni Fuad Lubis; Nurhayati Daulay; Siti Rohima Simatupang (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Household waste management, especially organic waste, remains a major problem in many regions, including Pematang Guntung Village, Teluk Mengkudu District, Serdang Bedagai Regency. Improperly managed organic waste has the potential to cause unpleasant odors, environmental pollution, and become a source of disease. Therefore, an appropriate and environmentally friendly solution is needed to overcome this issue. This study aims to examine how the application of the biopore method can serve as a strategy to create a cleaner environment while simultaneously improving soil fertility. The research method used was qualitative, with data collection techniques including observation, interviews, and documentation. The data obtained were analyzed descriptively to illustrate the implementation of biopores in the community. The results showed that the application of biopores was able to significantly reduce the volume of household organic waste. Organic waste placed into biopore holes naturally decomposed into compost, which is beneficial as an environmentally friendly fertilizer. In addition, biopores improved soil water absorption capacity, which helps reduce waterlogging during the rainy season and maintain soil moisture. From a social perspective, biopores encouraged the development of new awareness among community members regarding the importance of waste management. This was demonstrated by the active participation of residents in creating, utilizing, and maintaining biopore holes sustainably. Thus, biopores function not only as a technical solution for organic waste management but also as an environmental education tool that strengthens community collaboration in maintaining cleanliness and enhancing soil fertility in their area.